(3GYJQGV dTGg LdHi Ydi MLI TQYjI hcJHgG Ydi LdHi bfGdi RGOgs - (3TGg LdHjs ((3CHh GdSYhO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi MaX GdOjf hHYO agPg QSGdI CKHfG HGdHjGf HYV GdgahGJ GdUGOQg Yf HYV GdbVGg ef GdJMQja ddTQY GdTQja s
(3BNQgG (B:s
(3hde jOQ Cf GdQLhY Edi GdMb NjQ ef GdJeGOi Ydi GdHGWd Nha GdEedGb hGdEWfGH hGddg eY eajV GdMb hedge GdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3abg Mfais
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs